2007
DOI: 10.1111/j.1464-5491.2007.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of pioglitazone and voglibose on circulating total and high‐molecular‐weight adiponectin, and on two fibrinolysis inhibitors, in patients with Type 2 diabetes

Abstract: Increased serum HMW adiponectin may contribute to the improvement in glycaemic control after pioglitazone treatment. Plasma PAI-1 and TAFI were unchanged by either drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
4
11
1
Order By: Relevance
“…Our findings were at variance with another study which showed that pioglitazone did not reduce significantly plasma PAI-1 levels, despite elevations in adiponectin, 28 although a trend of reduction was apparent. It should be noted that the previous study involved half our sample size and treatment duration, and a relatively lower treatment dose, and the authors conceded that the baseline PAI-1 levels of their patients may not be high enough to accurately assess the lowering effect of pioglitazone.…”
Section: Discussioncontrasting
confidence: 57%
“…Our findings were at variance with another study which showed that pioglitazone did not reduce significantly plasma PAI-1 levels, despite elevations in adiponectin, 28 although a trend of reduction was apparent. It should be noted that the previous study involved half our sample size and treatment duration, and a relatively lower treatment dose, and the authors conceded that the baseline PAI-1 levels of their patients may not be high enough to accurately assess the lowering effect of pioglitazone.…”
Section: Discussioncontrasting
confidence: 57%
“…We also excluded patients with renal dysfunction (serum creatinine concentration >1.3 mg/dL) or liver dysfunction. Patients receiving treatment with peroxisome proliferatoractivated receptor (PPAR)-γ agonists, which increase the serum HMW adiponectin level, were also excluded (31).…”
Section: Methodsmentioning
confidence: 99%
“…Co r r e l a t i o n b e t we e n S e r u m HMW ADP N L e v e l s a n d Cl i n i c a l P a r (25). It is noteworthy that serum ADPN levels are increased in type 1 diabetes patients (26).…”
Section: T a B L E 3 Co Mp A R I S O N O F Cl I N I C A L A N D B Imentioning
confidence: 99%